1989
DOI: 10.1073/pnas.86.21.8545
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity in mice of an immunotoxin made with anti-transferrin receptor and a recombinant form of Pseudomonas exotoxin.

Abstract: LysPE40 is a modified form of Pseudomonas exotoxin that lacks the cell-binding domain and has a chemically reactive lysine residue near the amino terminus. LysPE40 is made in Escherichia coli and secreted into the medium from which it is readily purified. Two immunotoxins were constructed by coupling LysPE40 to an antibody to the human transferrin receptor (TFR) or to an antibody to the human interleukin-2 receptor. These immunotoxins were selectively cytotoxic to receptor-bearing cells in tissue culture. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 17 publications
0
54
0
Order By: Relevance
“…The use of Tf-adriamycin in a preliminary clinical study in acute leukemia patients has been reported [17]. A promising further application in vivo has been reported using the immunotoxin antiTfR-LysPE40, where intraperitoneal administration caused regression of subcutaneous A431 tumors [54].…”
Section: Targeting To Various Cell Types Via the Transferrin Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Tf-adriamycin in a preliminary clinical study in acute leukemia patients has been reported [17]. A promising further application in vivo has been reported using the immunotoxin antiTfR-LysPE40, where intraperitoneal administration caused regression of subcutaneous A431 tumors [54].…”
Section: Targeting To Various Cell Types Via the Transferrin Receptormentioning
confidence: 99%
“…Moreover, the Tf-conjugate, unlike native DT, was also highly toxic to murine cells. Pastan and co-workers [54] constructed the targetcell-specific immunotoxin antiTfR-LysPE40 by conjugation of antiTfR antibodies with recombinant 40-kDa fragments of Pseudomonas exotoxin that lack its cell-binding domain.…”
Section: Tf and Tfr Conjugates For Improved Uptake Into Cellsmentioning
confidence: 99%
“…[17][18][19][20]48,49 Given this background, we tested our hypothesis that a similar targeting strategy might be successful when directed to rapidly proliferating but nontransformed smooth muscle cells. To this end, we determined whether TGFa-PE40, a chimeric toxin previously found to be extremely potent in killing certain cancer cells,20 would be cytotoxic to rapidly proliferating smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…'1-14 This characteristic of certain transformed cells stimulated the development of cytotoxic agents specifically targeted to the cancer cells that overexpress these receptors. [15][16][17][18][19][20] We speculated that because activated smooth muscle cells also express higher numbers of certain cell surface receptors than do nonactivated cells, their excessive growth might be controlled by an analogous therapeutic approach.…”
mentioning
confidence: 99%
“…528) was generously provided by J. Mendelson (Masui et al 1984}. A conjugate (anti-EGFR-PE) of this antibody with Pseudomonas exotoxin (as a hapten) was the generous gift of I. Pastan and J. Batra (Batra et al 1989). The labeling sequence was as follows: anti-EGFR-PE at 1 ~g/ml, rabbit anti-Pseudomonas exotoxin (anti-PE) (the generous gift of D. FitzGerald and I. Pastan) at 2 ~g/ml, and goat anti-rabbit immunoglobulin G conjugated with either horseradish peroxidase (5 ~g/ml; Jackson ImmunoResearch) or 1 nm of colloidal gold (Janssen Auroprobe; 1 : 100 dilution); labeling was done at room temperature for 60 min.…”
Section: Histology and Immunocytochemistrymentioning
confidence: 99%